Disparate Impacts: Balancing the Need for Safe Schools With Racial Equity in Discipline. (October 2019) - Johnson, Odis; Jabbari, Jason; Williams, Maya; Marcucci, Olivia
Policy responses to gun violence within K-12 school systems have not stopped the increasing frequency of their occurrence, but have instead increased racial and ethnic disparities in multiple forms of discipline. The crisis prevention policies that follow school shootings tend to exacerbate racial and ethnic discipline disparities (a) within schools as practitioners enact policies with discretion and bias, (b) between schools where policy is complicated by racial segregation, and (c) indirectly where academic consequences accrue to those who are not disciplined but attend schools with elevated school rates of discipline. Among the most promising policy alternatives to punitive disciplinary policy is restorative justice.